2008
DOI: 10.1080/17470210701402331
|View full text |Cite
|
Sign up to set email alerts
|

An Isolation Effect in Serial Memory for Spatial Information

Abstract: This paper reports the first demonstration of an isolation effect or von Restorff effect (von Restorff, 1933) in the context of a spatial-memory task: Short-term serial recall was enhanced for both the location and the serial position of one red dot presented amongst a sequence of otherwise black dots. When the serial position of the isolate was fixed, the spatial isolation effect only emerged when participants received a control block of trials before the block of isolation trials (Experiment 1). However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Therefore, although colour might be processed, it is not useful for retention. However, if one green item is embedded in a list of black items, recall performance for the green item increases drastically (e. g., Cimbalo, Capria, Neider, & Wilking, 1977;Guérard, Hughes, & Tremblay, 2008). In such a list, colour becomes discriminant and can be useful for retention (e.g., see Brown, Neath, & Chater, 2007;Brown, Preece, & Hulme, 2000;Nairne, 1990;Neath, 1999;Oberauer & Kliegl, 2006).…”
Section: The Isolation Effectmentioning
confidence: 99%
“…Therefore, although colour might be processed, it is not useful for retention. However, if one green item is embedded in a list of black items, recall performance for the green item increases drastically (e. g., Cimbalo, Capria, Neider, & Wilking, 1977;Guérard, Hughes, & Tremblay, 2008). In such a list, colour becomes discriminant and can be useful for retention (e.g., see Brown, Neath, & Chater, 2007;Brown, Preece, & Hulme, 2000;Nairne, 1990;Neath, 1999;Oberauer & Kliegl, 2006).…”
Section: The Isolation Effectmentioning
confidence: 99%
“…Kang, McDermott and Roediger (2007) demonstrated through their experiments that students remember more when answering questions on tests with their own words, rather than answering multiple-choice questions, working on a deeper processing level in the controlling part of the metacognitive process. Guérard, Hughes and Tremblay (2008) researched about the so-called von Restorff, or isolation, effect. The von Restorff effect means that people remember information better when they are distinct from its surrounding.…”
Section: Metacognitionmentioning
confidence: 99%
“…Recent work also suggests this effect extends to spatial information. For example, Guérard, Hughes, and Tremblay (2008) showed that short-term serial recall was enhanced for both the location and the serial position of a red dot when presented among a sequence of otherwise black dots, highlighting the role of distinctiveness in enhancing memory. Based on these studies, we can make predictions about how to maximize accuracy when busy servers deliver plates of food to specific rooms and table locations in a restaurant.…”
mentioning
confidence: 99%